1989
DOI: 10.1577/1548-8667(1989)001<0119:domatr>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Development of Monoclonal Antibodies that Recognize a Type-2 Specific and a Common Epitope on the Nucleoprotein of Infectious Hematopoietic Necrosis Virus

Abstract: Two monoclonal antibodies were produced against the nucleoproteins of two strains of infectious hematopoietic necrosis virus (IHNV), One antibody, 1NDW14D, obtained by immunizing BALB/c mice with the nucleoprotein from Dworshak IHNV strain DW2, universally recognized IHNV in tests of direct and indirect fluorescence. The second antibody, 2NH105B, obtained by immunization with the nucleoprotein from an IHNV strain isolated from rainbow trout Oncorhynchus mykiss (formerly Salmo gairdneri) in the Hagerman Valley,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…These investigations, reporting the extent of heterogeneity among selected IHNV field isolates, relied upon using biological (Mulcahy et al 1984), serological (Winton et al 1988, Ristow & Arnzen 1989 and biochemical techniques such as electrophoretic mobility of structural proteins (Hsu et al 1986), RNase T1 mapping (Oshima et al 1995), and nucleotide sequencing . These studies have indicated that different strains of IHNV exist and that phenotypic and genetic relatedness generally correlates with geographic origin.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigations, reporting the extent of heterogeneity among selected IHNV field isolates, relied upon using biological (Mulcahy et al 1984), serological (Winton et al 1988, Ristow & Arnzen 1989 and biochemical techniques such as electrophoretic mobility of structural proteins (Hsu et al 1986), RNase T1 mapping (Oshima et al 1995), and nucleotide sequencing . These studies have indicated that different strains of IHNV exist and that phenotypic and genetic relatedness generally correlates with geographic origin.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…In order to correlate the phylogenetic types found in this study with an established monoclonal antibody typing system as described in Ristow & Arnzen (1989), 45 (20 M clade and 25 U clade isolates) of the 120 Columbia River basin isolates were tested for reactivity with the the type 2-specific monoclonal antibody 2NH105B (data not shown). This antibody binds to an unidentified epitope in the IHNV N protein of electropherotype 2 IHNV isolates.…”
Section: Correlation With Previous Ihnv Typing Systemsmentioning
confidence: 99%
“…The IHNV genome contains six genes in the order 39-N-P-M-G-NV-L-59, representing the nucleocapsid, phosphoprotein, matrix protein, glycoprotein, non-virion protein and polymerase protein genes, respectively (Kurath et al, 1985;Morzunov et al, 1995). Phenotypic and genetic diversity among IHNV isolates from different geographical sources have been investigated since the 1980s using various methods, including protein electropherotyping (Hsu et al, 1986), monoclonal antibody reactivity (Ristow & Arnzen, 1989;Ristow & Arnzen de Avila, 1991;Winton et al, 1988;LaPatra et al, 1994) and RNase T1 fingerprinting (Oshima et al, 1995). Phylogenetic analyses of the complete glycoprotein and non-virion protein gene sequences of twelve IHNV isolates confirmed the earlier studies in concluding that IHNV genetic types correlate with geography .…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal antibodies: Monoclonal antibodies to the glycoproteins and nucleoproteins of a number of different isolates of IHN virus were produced as descri.bed previously (Ristow & Arnzen 1989, &stow & Arnzen de Avila 1991. In this study, 6 of these rnonoclonal antibodies were utilized in indirect fluorescence to screen the French isolates: lNDWl4D (produced by an immunization with the nucleoprotein of a Dworshak isolate 2 and found to react with all 28 North American isolates tested); 1NDWl9I (also produced from an immunization to Dworshak isolate nucleoprotein, but not reacting with all North American isolates); 1NC027G (an anti-nucleoprotein antibody produced from a fusion against a Coleman isolate from chinook salmon Oncorhynchus tshawytscha); 3GH127B and 1NH139P (anti-glycoprotein and anti-nucleoprotein antibodies produced in a fusion in which the glycoprotein and the nucleoprotein of Hagerman virus, isolate 039-82SR, were the respective immunogens); and 2NH105B (an anti-nucleoprotein antibody made by immunization with the nucleoprotein of Hagerman virus 039-82SR), which recognizes electrophoretic type 2 IHNV (Hsu et al 1986, Ristow & Arnzen 1989.…”
Section: Infectious Haematopoietic Necrosis Virus (Ihnv) Ismentioning
confidence: 99%